Emotional and behavioral alterations and their relationship with executive functioning in the pediatric population with autism spectrum disorder and epilepsy: a comparative study - Cano-Villagrasa, Alejandro; Moya-Faz, Francisco J.; Cortés-Ramos, Antonio; López-Zamora, Miguel (Frontiers in Psychology, 2023)
Introduction. The pediatric population with Autism Spectrum Disorder (ASD) and epilepsy presents behavioral and emotional alterations that hinder their correct developmental maturation as well as their integration in different contexts such as school, family or social. This population shows atypical behavioral and emotional patterns, with difficulties in emotional regulation, understanding of emotions, aggressiveness, or low frustration tolerance. They also present alterations in executive functions, which significantly influence the emotional and behavioral characteristics of this population.Research suggests that epilepsy worsens the emotional, behavioral, and executive functioning status.Objective. To explore differences in behavioral, emotional, and executive functioning profile in individuals with a diagnosis of ASD, epilepsy, and ASD with epilepsy.Method. In this quasi-experimental and cross-sectional study, a total of 170 participants were selected and distributed into three groups: a group of participants with ASD, a group with epilepsy, and a group of participants with ASD and epilepsy. The SENA, BASC-3, and ENFEN tests were administered to verify the behavioral, emotional, and executive functioning profile in the three groups.The results indicate that individuals diagnosed with ASD and epilepsy present greater emotional, behavioral, and executive functioning alterations compared to those who only present ASD or epilepsy.Individuals with ASD and epilepsy present significant alterations in emotional, behavioral, and executive functioning processes, which hinder their adaptation to different contexts, as well as decreasing their quality of life and that of their family.